2022
DOI: 10.3390/ijms23063397
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Bases of the Interaction between a Saponin from the Roots of Gypsophila paniculata L. and Model Lipid Membranes

Abstract: In view of the possible medical applications of saponins, the molecular structure of a GOTCAB saponin from the roots of Gypsophila paniculata L. was determined by NMR. The biological activity of saponins may depend on the interaction with cell membranes. To obtain more insight in the mechanism of membrane-related saponin function, an experimental and theoretical study was conducted. Ternary lipid systems composed of sphingomyelin, 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine, and cholesterol were used as m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…[1][2][3] Especially, saponins are important bioactive compounds, mainly obtained from the roots of Gypsophila species. [4][5][6][7] The triterpenoid saponins from Gypsophila plant species were reported to have remarkable biological activities, including anticarcinogenic, [8,9] anti-inflammatory, [10] antitumor, [11][12][13] antiproliferative, [14] antioxidant activities. [15,16] Therefore, the roots that contain rich saponins of the Gypsophila species can be considered as a valuable source.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Especially, saponins are important bioactive compounds, mainly obtained from the roots of Gypsophila species. [4][5][6][7] The triterpenoid saponins from Gypsophila plant species were reported to have remarkable biological activities, including anticarcinogenic, [8,9] anti-inflammatory, [10] antitumor, [11][12][13] antiproliferative, [14] antioxidant activities. [15,16] Therefore, the roots that contain rich saponins of the Gypsophila species can be considered as a valuable source.…”
Section: Introductionmentioning
confidence: 99%
“…They give insight into atomistic/molecular details which are unavailable to direct experimental measurements. In some of our previous works, we have demonstrated that MD simulations can be helpful in studying drug-membrane interactions [41,42]. They were also successfully used in studies of the interactions between NRTIs and reverse transcriptase [43][44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%